Control of White Spot Lesions with Use of Fluoride Varnish or Chlorhexidine Gel During Orthodontic Treatment A Randomized Clinical Trial - Restrepo, M. [UNESP]; Bussaneli, D. G. [UNESP]; Jeremias, F. [UNESP]; Cordeiro, R. C. L. [UNESP]; Raveli, D. B. [UNESP]; Magalhaes, A. C.; Candolo, C.; Santos-Pinto, L. [UNESP] (Journal Pedodontics Inc, 2016)
Objective: To compare the effectiveness of fluoride varnish and 2% chlorhexidine gel for controlling active white spot lesions (WSLs) adjacent to orthodontic brackets. Study design: Thirty-five orthodontic patients (17.2+/-2.3 years old) presenting 60 WSLs adjacent to orthodontic brackets were enrolled in this randomized, blind, 3-armed and controlled clinical trial. The patients were randomly allocated to 1 of 3 arms: (1) two applications of 5% NaF varnish- F, with one-week interval, (2) two applications of 2% chlorhexidine gel-CHX, with one-week interval and (3) usual home care-control (CO). The WSLs were scored by using a DIAGNOdent pen. An independent examiner scored the surfaces using Nyvad criteria for caries assessment. Results: A total of thirty patients presenting 51 lesions completed the study. All treatments reduced the fluorescence values during the experimental period; however, F induced faster remineralization than CHX. After 3 months, 70.58 % were inactive considering all groups. DIAGNOdent pen and Nyvad presented a significant correlation. Conclusion: After 3 months of treatment, F, CHX and CO were capable of controlling the WSLs adjacent to the orthodontic brackets. However, the treatment with F was capable of controlling the progression of the WSLs in a shorter period of time.
Keywords: Chlorhexidine; Dental Caries; Fluorescence; Fluoride; Orthodontic Appliances; Tooth remineralization